TOXICOLOGICAL EVALUATION AND IN SILICO PHARMACOKINETICS OF CEFTIOFUR IN HUMAN AND ENVIRONMENTAL HEALTH - Correa , Gabriel Veloso; Rosa, José Felipe Leite Ferreira; Cezário, Stephanie Priscila de Sousa; Araujo, Laura Faria; Prates, Ludmilla Louise Cerqueira Maia; Nobre, Sérgio Avelino Mota; Motta, Luiz Frederico (Seven Editora, 2024)
Ceftiofur is a broad-spectrum cephalosporin, effective against Gram-positive and Gram-negative pathogens. This antibiotic works by inhibiting the synthesis of the bacterial cell wall. Antibiotics, used in both human and veterinary medicine, are drugs of concern when found in the environment. This is due to the fact that, even at low concentrations, prolonged exposure to these residues can lead to the emergence of resistant bacteria, compromising human health and environmental balance. Direct or indirect contact, whether through the food chain, water resources or animal excreta, represent the main routes of contamination. In the present study, in silico methodologies were employed  to predict the molecular properties of the antibiotic Ceftiofur. The in silico environmental toxicology study  showed that Ceftiofur is not toxic to bees, but is toxic to fish and crustaceans, and its chemical structure does not degrade in the environment. ADME in silico analysis  indicated that the antibiotic does not present a favorable prediction for oral bioavailability, due to violations of the Lipinski criteria and has a moderate intestinal absorption rate and absence of permeability across the blood-brain barrier. In addition, the in silico pharmacokinetic study  revealed that Ceftiofur has no inhibitory capacity on any of the five hepatic isoenzymes of cytochrome P450 complex (CYP450). The  human in silico toxicology study  showed promising results, demonstrating that the antibiotic is non-toxic (non-mutagenic) in the AMES test, has no carcinogenic properties, and is classified in category IV for acute oral toxicity, indicating low toxicity. DOI:https://doi.org/10.56238/sevened2024.037-107